A single mutation in Crimean-Congo hemorrhagic fever virus discovered in ticks impairs infectivity in human cells - Hua, Brian L; Scholte, Florine EM; Ohlendorf, Valerie; Kopp, Anne; Marklewitz, Marco; Drosten, Christian; Nichol, Stuart T; Spiropoulou, Christina; Junglen, Sandra; Bergeron, Éric (eLife, 2020)
Crimean-Congo hemorrhagic fever (CCHF) is the most widely distributed tick-borne viral infection in the world. Strikingly, reported mortality rates for CCHF are extremely variable, ranging from 5% to 80% (Whitehouse, 2004). CCHF virus (CCHFV, Nairoviridae ) exhibits extensive genomic sequence diversity across strains (Deyde et al., 2006; Sherifi et al., 2014). It is currently unknown if genomic diversity is a factor contributing to variation in its pathogenicity. We obtained complete genome sequences of CCHFV directly from the tick reservoir. These new strains belong to a solitary lineage named Europe 2 that is circumstantially reputed to be less pathogenic than the epidemic strains from Europe 1 lineage. We identified a single tick-specific amino acid variant in the viral glycoprotein region that dramatically reduces its fusion activity in human cells, providing evidence that a glycoprotein precursor variant, present in ticks, has severely impaired function in human cells. Crimean-Congo hemorrhagic fever (CCHF) is caused by infection with a virus spread by ticks in Europe, Africa and Asia. It can cause severe disease in humans, including high fevers and bleeding. How deadly CCHF is varies with between 5% to 80% of those infected dying. Scientists suspect genetic differences in various strains of the virus may account for the differences in death rates, but they do not know the exact mutations that make the CCHF virus more or less deadly. To learn more, scientists have sorted strains of CCHF virus into different groups based on how similar they are genetically. One group called Europe 2 infects many people in the Balkans, but it rarely causes illness. In fact, only two mild cases of illness have been associated with Europe 2 strains, while other CCHF virus strains circulating in this region have caused thousands of more severe illnesses. Now, Hua et al. identified a mutation in one Europe 2 strain of the CCHF virus that may explain why this subgroup of viruses rarely causes severe human disease. The researchers collected a strain of CCHF virus from infected ticks found in Bulgaria and sequenced its genome. They named the virus strain Malko Tarnovo. Through a series of experiments, Hua et al. showed that the Malko Tarnovo strain very efficiently infects tick cells but not human cells. A single amino acid change in the genetic sequence of the virus appears to make the virus less able to infect human cells. The mutation prevents a protein on the surface of the virus from fusing with human cells, an essential step in infection. This may explain why this strain and others in the Europe 2 group do not cause severe human disease. Hua et al. also demonstrate the importance of studying viruses in the animals that spread them. By studying the CCHF virus in ticks, scientists may be able to learn more about how viruses evolve to infect new species, which may help scientists prevent future pandemics.